Analysis Of MSME Performance To Improve Consumer Satisfaction - Muchammad Riky Ramadhani; Kholifatul Fitria; Deka, Rio Era (International Journal of Entrepreneur and Business Administration, 2024)
The aim of carrying out this research is to analyze the internal performance of Mojokkopi MSMEs within Begawan Apartments, which highlights the best side of Mojokkopi's internal performance as a business strategy. Data collection for this research was carried out using interview methods and direct observation of MSMEs, which are described in qualitative research methods.. The results of this research are that Mojokkopi has an interesting internal aspect, the developments they have made have experienced very significant differences from when they were founded until now. And currently Mojokkopi can compete with well-known internal tenants in Begawan Apartments.